Measurements of jet charge with dijet events in pp collisions at √s=8 TeV(Article) The CMS collaboration, - CMS, The CMS collaboration; Sirunyan, A. M.; Tumasyan, A. R.; Adam, Wolfgang; Asilar, Ece; Md. Ali, Mohd. Adli (Springer Verlag, 2017)
Jet charge is an estimator of the electric charge of a quark, antiquark, or gluon initiating a jet. It is based on the momentum-weighted sum of the electric charges of the jet constituents. Measurements of three charge observables of the leading jet in transverse momentum pT are performed with dijet events. The analysis is carried out with ata collected by the CMS experiment at the CERN LHC in proton-proton collisions at s=8 TeV corresponding to an integrated luminosity of 19.7fb−1. The results are presented as a function of the pT of the leading jet and compared to predictions from leading- and next-to-leading-order event generators combined with parton showers. Measured jet charge distributions, unfolded for detector effects, are reported, which expand on previous measurements of the jet charge average and standard deviation in pp collisions.